Angiolymphoid Hyperplasia - A Case Report - M Patel; R Mahajan; K Ninama; F E Bilimoria (Journal of Integrated Health Sciences)
Angiolymphoid hyperplasia with eosinophilia consists of erythematous papules and nodules involving the head and neck, though the other sites may also be involved. Here we present a case of 50 year old female patient who presented with pruritic papules on the pinna since 6-7 months, which on histopathology revealed features of angiolymphoid hyperplasia. Her lesions were ablated with Carbon dioxide laser in 2 sittings, with no recurrence of lesions over a 1 year follow up period.